Regimes of Biomolecular Ultrasmall Nanoparticle Interactions. Issue 15 (15th March 2017) - Boselli, Luca; Polo, Ester; Castagnola, Valentina; Dawson, Kenneth A.
Abstract: Ultrasmall nanoparticles (USNPs), usually defined as NPs with core in the size range 1–3 nm, are a class of nanomaterials which show unique physicochemical properties, often different from larger NPs of the same material. Moreover, there are also indications that USNPs might have distinct properties in their biological interactions. For example, recent in vivo experiments suggest that some USNPs escape the liver, spleen, and kidney, in contrast to larger NPs that are strongly accumulated in the liver. Here, we present a simple approach to study the biomolecular interactions at the USNPs bio‐nanointerface, opening up the possibility to systematically link these observations to microscopic molecular principles. Abstract : Ultrasmall nanoparticles were synthesized to study size and ligand effects on the formation of the protein corona. The interactions of the ultrasmall nanoparticles in a relevant biological milieu were investigated, opening up the possibility to systematically link these observations to microscopic molecular principles.